2014
DOI: 10.1016/j.applanim.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of welfare outcomes for weaner and mature Bos indicus bulls surgically or tension band castrated with or without analgesia: 2. Responses related to stress, health and productivity

Abstract: a b s t r a c tTension banding castration of cattle is gaining favour because it is relatively simple to perform and is promoted by retailers of the banders as a humane castration method. Two experiments were conducted, under tropical conditions using Bos indicus bulls comparing tension banding (Band) and surgical (Surgical) castration of weaner (7-10 months old) and mature (22-25 months old) bulls with and without pain management (NSAID (ketoprofen) or saline injected intramuscularly immediately prior to cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…In a cattle castration study conducted by Petherick et al (2014aPetherick et al ( , 2014b, it was found that castration using tension banding caused a delayed response in Hp compared with surgical castration and the responses were also correlated with the progression of wound healing. Review of the literature reveals that IL-1 and IL-6 stimulates the release of APP from the liver to restore the normal body functions following tissue injury.…”
Section: Structure Of Thesismentioning
confidence: 99%
See 4 more Smart Citations
“…In a cattle castration study conducted by Petherick et al (2014aPetherick et al ( , 2014b, it was found that castration using tension banding caused a delayed response in Hp compared with surgical castration and the responses were also correlated with the progression of wound healing. Review of the literature reveals that IL-1 and IL-6 stimulates the release of APP from the liver to restore the normal body functions following tissue injury.…”
Section: Structure Of Thesismentioning
confidence: 99%
“…Shutt et al (1988a) and Paull et al (2009) evaluated the cortisol response and the presence of pain-related behaviour in animals which was marked within hours up to 1-2 days of post-treatment. However, studies in cattle castration comparing surgical and tension banding techniques had found that surgical castration caused acute pain, whereas banding caused delay in the pain response, which may be detected weeks after castration (Moya et al, 2014;Petherick et al, 2014b). Gregory (2004) described the application of tourniquet on appendages such as castration and tailing by rubber rings causes an immediate pain sensation following the application, and progresses into an inflammatory pain, which is also described as ischaemic pain.…”
Section: Pain and Stress In Ruminants Caused By Routine Husbandry Promentioning
confidence: 99%
See 3 more Smart Citations